Respuesta :
3] 4 -5 2 11
12 21 69
----------------------
4 7 23 80
80 would be the remainder
Another method would be to plug 3 into the equation for x
[tex]4(3)^{3}-5(3)^{2}+2(3)+11[/tex] = 4(27) - 5(9) + 6 + 11 = 108 - 45 + 6 + 11 = 63 + 6 + 11 = 80
12 21 69
----------------------
4 7 23 80
80 would be the remainder
Another method would be to plug 3 into the equation for x
[tex]4(3)^{3}-5(3)^{2}+2(3)+11[/tex] = 4(27) - 5(9) + 6 + 11 = 108 - 45 + 6 + 11 = 63 + 6 + 11 = 80
Answer:
The remainder is 80
Step-by-step explanation:
Given the polynomial
[tex]f(x)=4x^3-5x^2+2x+11[/tex]
we have to find the remainder when the above polynomial f(x) is divided by x-3
By remainder theorem when we put x=3 in f(x) we get the remainder i.e f(3)
[tex]f(3)=4(3)^3-5(3)^2+2(3)+11[/tex]
[tex]=108-45+6+11[/tex]
[tex]=80[/tex]
which is required remainder.
Hence, the remainder is 80